7th International Conference on Environment and Industrial Innovation. (May 2017) - Unknown
Abstract : Preface It is our great pleasure to welcome you to 2017 7th International Conference on Environment and Industrial Innovation (ICEII 2017) which was held in International University of Malaya Wales, Kuala Lumpur, Malaysia during April 24-26, 2017. ICEII 2017 is dedicated to issues related to Environment and Industrial Innovation. The major goal and feature of the conference is to bring academic scientists, engineers, industry researchers together to exchange and share their experiences and research results, and discuss the practical challenges encountered and the solutions adopted. Professors from Malaysia, Canada, Thailand are invited to deliver keynote speeches regarding latest information in their respective expertise areas. It will be a golden opportunity for the students, researchers and engineers to interact with the experts and specialists to get their advice or consultation on technical matters, sales and marketing strategies. This proceedings present a selection from papers submitted to the conference from universities, research institutes and industries. All of the papers were subjected to peer-review by conference committee members and international reviewers. The papers selected depended on their quality and their relevancy to the conference. The volume tends to present to the readers the recent advances in the field of Environment and Industrial Innovation and various related areas, such as Advanced Ceramic-porous ceramic, Aerodynamics, Application of Spatial technology, Catalysis and Environment, Enivronmental Biotechnology, Environment management, Environmental Chemistry, Environmental engineering, Environmental Planning of Mines, Environmental Pollution Control, Fermentation Technology, Industrial Environment, etc.. We would like to thank all the authors who have contributed to this volume and also to the organizing committee, reviewers, speakers, chairpersons, sponsors and all the conference participants for their support to ICEII 2017. Prof. Koh Hock Lye Sunway University, Malaysia April. 5, 2017